HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PENGOBATAN TUBERCULOSIS PARU DI RUMAH SAKIT PARU DUNGUS MADIUN - YULIANA, FITRIA (Journal Nursing Care and Biomolecular, 2019)
Introduction: The World Health Organization (WHO) was stated after the Mantoux test 1: 3 the world population has approve by M. Tuberculosa. Because TB or commonly call Acid Resistant Bacteria is a health problem that is very problematic in the world and a global emergency problem. (Hutapea, 2009). Methods: This study uses Correlation design with Cross Sectional model. Observation and data retrieval process was done at one time to determine the results of the study. The study population was patients with pulmonary TB at Dungus?s Hospital. This study used a sampling technique with simple random sampling obtained by 55 respondents. Data analysis used was univariate and bivariate analysis using c-square test. Results and Analysis: Identification of family support for treatment in pulmonary tuberculosis patients at Dungus Madiun Hospital showed results of family support of 85.4% or 47 respondents supporting good families. Treatment compliance of patients with pulmonary TB at Dungus Madiun Hospital shows 89.1% in the treatment of pulmonary TB in RSP Dungus. The results of the analysis of the relationship of family support with the treatment of pulmonary TB at Dungus Madiun Hospital based on the results of testing the above data shows a significant value r-value = 0,000 means the hypothesis is accepted. Discuss: It have relationship between family support and treatment approval in Lung Tuberculosis patients at Dungus Madiun Hospital.